Fruit and vegetable consumption and all-cause, cancer and CVD mortality: analysis of Health Survey for England data. Issue 9 (31st March 2014) - Oyebode, Oyinlola; Gordon-Dseagu, Vanessa; Walker, Alice; Mindell, Jennifer S
Abstract : Background: Governments worldwide recommend daily consumption of fruit and vegetables. We examine whether this benefits health in the general population of England. Methods: Cox regression was used to estimate HRs and 95% CI for an association between fruit and vegetable consumption and all-cause, cancer and cardiovascular mortality, adjusting for age, sex, social class, education, BMI, alcohol consumption and physical activity, in 65 226 participants aged 35+ years in the 2001–2008 Health Surveys for England, annual surveys of nationally representative random samples of the non-institutionalised population of England linked to mortality data (median follow-up: 7.7 years). Results: Fruit and vegetable consumption was associated with decreased all-cause mortality (adjusted HR for 7+ portions 0.67 (95% CI 0.58 to 0.78), reference category <1 portion). This association was more pronounced when excluding deaths within a year of baseline (0.58 (0.46 to 0.71)). Fruit and vegetable consumption was associated with reduced cancer (0.75 (0.59–0.96)) and cardiovascular mortality (0.69 (0.53 to 0.88)). Vegetables may have a stronger association with mortality than fruit (HR for 2 to 3 portions 0.81 (0.73 to 0.89) and 0.90 (0.82 to 0.98), respectively). Consumption of vegetables (0.85 (0.81 to 0.89) per portion) or salad (0.87 (0.82 to 0.92) per portion) were most protective, while frozen/canned fruit consumption was apparently associated with increased mortality (1.17 (1.07 to 1.28) per portion). Conclusions: A robust inverse association exists between fruit and vegetable consumption and mortality, with benefits seen in up to 7+ portions daily. Further investigations into the effects of different types of fruit and vegetables are warranted.